A unique TBX5 microdeletion with microinsertion detected in patient with Holt–Oram syndrome. (28th September 2015) - Morine, Mikio; Kohmoto, Tomohiro; Masuda, Kiyoshi; Inagaki, Hidehito; Watanabe, Miki; Naruto, Takuya; Kurahashi, Hiroki; Maeda, Kazuhisa; Imoto, Issei
Abstract : Holt–Oram syndrome (HOS) is an autosomal dominant condition characterized by upper limb and congenital heart defects and caused by numerous germline mutations of TBX5 producing preterminal stop codons. Here, we report on a novel and unusual heterozygous TBX5 microdeletion with microinsertion (microindel) mutation (c.627delinsGTGACTCAGGAAACGCTTTCCTGA), which is predicted to synthesize a truncated TBX5 protein, detected in a sporadic patient with clinical features of HOS prenatally diagnosed by ultrasonography. This uncommon and relatively large inserted sequence contains sequences derived from nearby but not adjacent templates on both sense and antisense strands, suggesting two possible models, which require no repeat sequences, causing this complex microindel through the bypass of large DNA adducts via an error‐prone DNA polymerase‐mediated translesion synthesis. © 2015 Wiley Periodicals, Inc.